Asymmetric Hydrolytic and Aminolytic Kinetic Resolution of Racemic Epoxides using Recyclable Macrocyclic Chiral Cobalt(III) Salen Complexes. Issue 22 (16th November 2017) - Tak, Rajkumar; Kumar, Manish; Menapara, Tusharkumar; Gupta, Naveen; Kureshy, Rukhsana I.; Khan, Noor‐ul H.; Suresh, E.
Abstract: New chiral macrocyclic cobalt(III) salen complexes were synthesized and used as catalyst for the asymmetric kinetic resolution (AKR) of terminal epoxides and glycidyl ethers with aromatic/aliphatic amines and water as nucleophiles. This is the first occasion where a Co(III) salen complex demonstrated its ability to catalyze AKR as well as hydrolytic kinetic resolution (HKR) reactions. Excellent enantiomeric excesses of the epoxides, the corresponding amino alcohols and diols (upto 99%) with quantitative yields were achieved by using the chiral Co(III) salen complexes in dichloromethane at room temperature. This protocol was further extended for the synthesis of two important drug molecules, i.e., ( S )‐propranolol and ( R )‐naftopidil. The catalytic system was also explored for the synthesis of chirally pure diols and chiral cyclic carbonates using carbon dioxide as a greener renewable C1 source. The catalyst was recycled for upto 5 catalytic cycles with retention of enantioselectivity. Abstract :